Effects of Intermittent Compared With Continuous Energy Restriction on Blood Pressure Control in Overweight and Obese Patients With Hypertension - He, Chao-Jie; Fei, Ye-Ping; Zhu, Chun-Yan; Yao, Ming; Qian, Gang; Hu, Hui-Lin; Zhai, Chang-Lin (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Weight-loss diets reduce body weight and improve blood pressure control in hypertensive patients. Intermittent energy restriction (IER) is an alternative to continuous energy restriction (CER) for weight reduction. We aimed to compare the effects of IER with those of CER on blood pressure control and weight loss in overweight and obese patients with hypertension during a 6-month period. Methods: Two hundred and five overweight or obese participants (BMI 28.7 kg/m2) with hypertension were randomized to IER (5:2 diet, a very-low-calorie diet for 2 days per week, 500 kcal/day for women and 600 kcal/day for men, along with 5 days of a habitual diet) compared to a moderate CER diet (1000 kcal/day for women and 1200 kcal/day for men) for 6 months. The primary outcomes of this study were changes in blood pressure and weight, and the secondary outcomes were changes in body composition, glycosylated hemoglobin A1c (HbA1c), and blood lipids. Results: Of the 205 randomized participants (118 women and 87 men; mean [SD] age, 50.2 [8.9] years; mean [SD] body mass index, 28.7 [2.6]; mean [SD] systolic blood pressure, 143 [10] mmHg; and mean [SD] diastolic blood pressure, 91 [9] mmHg), 173 completed the study. The intention-to-treat analysis demonstrated that IER and CER are equally effective for weight loss and blood pressure control: the mean (SEM) weight change with IER was -7.0 [0.6] kg vs. -6.8 [0.6] kg with CER, the mean (SEM) systolic blood pressure with IER was -7 [0.7] mmHg vs. -7 [0.6] mmHg with CER, and the mean (SEM) diastolic blood pressure with IER was -6 [0.5] mmHg vs. -5 [0.5] mmHg with CER, (diet by time P = 0.62, 0.39, and 0.41, respectively). There were favorable improvements in body composition, HbA1c, and blood lipid levels, with no differences between groups. Effects did not differ according to completer analysis. No severe hypoglycemia occurred in either group during the trial. Conclusions: Intermittent energy restriction is an effective alternative diet strategy for weight loss and blood pressure control and is comparable to CER in overweight and obese patients with hypertension.